Understanding the intersecting social, technical, and ecological systems challenges associated with emerging contaminants in drinking water using cyanotoxins as an example - Christine J. Kirchhoff; Cristina Mullin; Reginald Denny; Maria Carmen Lemos; Galen Treuer (Journal of Infrastructure Preservation and Resilience)
Abstract This paper investigates toxic algal blooms (TABs) and their management as an example of a complex emerging contaminant (EC) problem through the lens of interconnected social, technical, ecological systems (SETS). We use mixed methods including analysis of a national survey of public drinking water systems and interviews with drinking water managers and state regulators. For the first time, we extend SETS to the drinking water context to advance a holistic understanding of the complexity of TABs as a problem for drinking water systems and identify specific intervention points to ease TABs management difficulty. We find that management challenges arise at the intersection of SET domains, and often coincide with circumstances where water managers and existing technologies are pushed outside of their traditional operating spheres or when new technologies are introduced creating cascading SET challenges. ECs that do not behave like traditional contaminants and pollutants require adapting social and technical systems to be responsive to these differences. Understanding how management difficulties arise within SET domains and their intersections will help drinking water managers and state regulators mitigate management difficulties in the future. These findings have implications for understanding and mitigating other EC management challenges as well.